Learning Sources Management Based on the Four Principles of Kindly Treatment for Life–long learning Schools under Amnat Charoen Informal and Non–Formal Education Promotion Office - Sangbunsri, Wanna; Phrakruchayaratanakon; Silpanilmalaya, Anake (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study learning source management based on the four principles for kindly treatment for lifelong learning in schools under Amnat Charoen Informal and non-formal education promotion office, 2) to compare the so-said administration, 3) to compile the related recommendations as suggested by the respondents. The sampling groups acting as informants comprised informal and non-formal education teachers and advisory panels to their respective schools, totally 105 in number. The device used to collect the information was the five-rating scale questioner. The Statistical tools employed for data analysis were percentage, means, S.D., t-tests (Independent Samples), and F-test (One way ANOVA) The research results were as follows : 1. Levels of school administrators’ learning source managements based on Buddhism’s Four Principles of Kindly Treatment for lifelong learning in schools under the above office have been rated ‘high’. 2) As classified by informants’ variables of gender, statues and age comparative results of their opinions on school administrators’ learning source managements involving Buddhism’s Four Principles of Kindly Treatment for lifelong learning in schools under the aforesaid office do not vary in the comprehensive aspects. 3) Informants have recommended the following opinions on enhancing school administrators’ learning source managements. Firstly, school administrators plan learning resource managements. Secondly, they support and develop personnel. Further, they hold regular training sessions for learning resource managements. Thirdly, they strongly encourage each of personnel to participate in tasks. Moreover, it is essential that they launch public relations and support every sector to take part in activities and continually supervise them. Finally, panels to each school must regulate, supervise and assess every activity their schools have undertaken.